Plasma Renin in ipsilateral renal vein in patients with chronic unilateral pelvic ureteric junction obstruction - Hanif, A; Hasina, K; Hassan, K; Islam, MS; Karim, MS; Alam, MU (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):543-8 The abstract of this article is available on the PubMed website